Effect of increased CO2 concentration on the growth rate of Isopora palifera and Acropora hyacinthus from different cross-shelf reef zones. (April 2019) - Yusuf, M Y; Rukminasari, N; Yanuarita, D; Jompa, J; Suharto
Abstract: The rise in atmospheric carbon dioxide (CO2) concentration due to emissions associated with economic development is altering ocean chemistry, a process known as ocean acidification. The resultant decrease in oceanic pH will affect marine organisms, in particular those which build their skeletons through calcification such as scleractinian corals. The aim of this research was to analyse the likely impact of changing CO2 concentrations and thus seawater pH on the growth rate of two common corals, Isopora palifera and Acropora hyacinthus . This research was conducted at the Marine, Coastal and Small Island Research Centre, Universitas Hasanuddin, Indonesia. Samples of Isopora palifera and Acropora hyacinthus were collected along an inshore-offshore cross-shelf gradient from 3 sites: Pulau Karanrang (inner zone), Pulau Badi (intermediate zone), and Pulau Kapoposang (outer zone). A fully randomised research design was used with three replicates for each of three CO2 treatments: 390 ppm (control), 550 ppm (2030 prediction), 1000 ppm (2050 prediction). The samples were weighed weekly for 1 month (digital balance, accuracy 0.1 mg). ANOVA analysis with post hoc Tukey Test showed a significant (p < 0.05) between treatment difference in growth rate for both Isopora palifera and Acropora hyacinthus (P<0, 05). The corals from all three zones exhibited positive growth at 390 ppm CO2, and negative growth at CO2 concentrations of 550 ppm and 1000 ppm.